Use of serum biomarkers in the diagnosis of traumatic brain injury - Nadira Nabiyeva Çevik; Ali Korulmaz; Mehmet Alakaya; Barış Ten; Çağrı Eroğlan; Mehmet Burak Yavuz Çimen; Ali Ertuğ Arslanköylü (Trends in Pediatrics)
Objective: Traumatic brain injury (TBI) is a leading cause of death and disability in the pediatric age group. This study aimed to investigate the effectiveness of serum S100 calcium-binding protein B (S100b), ubiquitin carboxyterminal hydrolase-like1 (UCH-L1), glial fibrillary acidic protein (GFAP), and neurofilament (NF) protein levels in predicting the diagnosis and prognosis of traumatic brain injury.